THE ROLE OF FINANCIAL DIGITIZATION IN THE PROFITABILITY OF THE BANKING SECTOR: THE EXPERIENCE OF IRAQ - Prof. Dr. Subhi Hassoon; Ammar Amer Khadim (Scholars Digest Publishing, 2024)
The study aims to highlight the extent of the development of profitability indicators for the Iraqi banking sector in light of the rapid developments in financial digital technologies. The study problem focused on the question (Is there a role for developing financial digitalization methods that contribute to increasing the profitability of the Iraqi banking sector?). The study assumed that the use, application or development of financial digitalization methods could contribute to increasing the profitability of the Iraqi banking sector. The study relied on the theoretical (descriptive) and analytical approach to the study sample data during the period (2011-2022), as it relied on data issued by the Central Bank of Iraq. The study came out with a set of results, most notably the existence of a partial contribution of financial digitalization channels to the profitability indicators of the Iraqi banking sector. The study concluded with a set of recommendations, most notably encouraging the adoption of digital financial products and spreading the culture of electronic payment, by launching media and marketing campaigns to highlight the advantages of products and using various channels such as social media and television, organizing training and educational courses to educate the public, and creating interactive digital platforms to educate and guide users through the use of technologies such as virtual reality and simulation.
Keywords: Financial digitization, financial digitization channels, profitability.